Enhanced visible-light photocatalytic activity of core-shell oxide nanoparticles synthesized by wet chemical precipitation and atomic layer deposition - Podurets, Anastasiia; Kolokolov, Daniil; Barr, Maissa; Ubyivovk, Eugenii; Osmolowsky, Mikhail; Bobrysheva, Natalia; Bachmann, Julien; Osmolovskaya, Olga (Applied Surface Science, 2020)
In this work, SnO2@MOx (MOx = ZnO, SnO2, TiO2) core-shell nanoparticles were synthesized by atomic layer deposition method (ALD) and characterized in terms of their structural, optical and photocatalytic properties. The band gap values are found to be in the range of 2.8 to 4.6 eV, whereby distinct values were demonstrated for the core and shell materials in the case of SnO2@SnO2 and SnO2@TiO2. Under UV and visible light irradiation, the as-prepared nanoparticles exhibited clearly distinct activities towards the photocatalytic degradation of methylene blue, depending on the structure and band gap values. Without using any multi-stage sample preparation, a full degradation of the pollutant model was achieved in 10 min with the novel particles, conditions in which simpler particles do not achieve a comparable performance. These results make the core-shell nanoparticles under study an applicable UV or visible-light photocatalyst for efficient environmental remediation photocatalysis.
CRIS-Team WoS Importer:2020-11-27